Modeling Loss of Microvascular Wall Homeostasis during Glycocalyx Deterioration and Hypertension that Impacts Plasma Filtration and Solute Exchange - Facchini, Laura; Bellin, Alberto; Toro, Eleuterio F. (Current Neurovascular Research, 2016)
The fiber matrix of the surface glycocalyx layer internally coating the endothelial cells and plugging the intercellular clefts is crucial for microvascular wall homeostasis. Disruption of the glycocalyx is found in clinical conditions characterized by microvascular and endothelial dysfunction such as atherosclerosis, diabetes mellitus, chronic renal failure and cerebrovascular disease. Shedding of its components may also occur during oxidative stress and systemic inflammatory states including septis. In this work, we investigate the effects of glycocalyx degradation, either due to enzymatic digestion or to agonist recruitment, on plasma filtration and solute extravasation. We also take into account the possibility of a physiological or pathological increase in blood pressure, as in hypertensive zones such as pre- and post-stenotic blood vessels. Our mathematical model shows that a seriously damaged glycocalyx produces an augmentation of flux of both solvent and solute, thus losing its role of transport barrier and macro-molecular sieve, in agreement with experimental evidence. Similarly, hypertension causes an increase in both volume and solute fluxes, also according to physiological findings. The combination of glycocalyx deterioration and hypertension further raises plasma and solute fluxes, potentially leading in most severe cases to edema and hemorrhage, as in the case of diabetes.
Keywords: Filtration